Neurosky EEG Biosensor Using in Education - Mehmet Tabakcıoğlu; Hüseyin ÇIZMECI; Doruk AYBERKIN (International Journal of Applied Methods in Electronics and Computers, 2016)
Brain is composed by neurons using electricity to communicate to each other. There is a great amount electrical activity in the brain due to collection of numerous neurons sending signal. Neurons send brainwaves detected by sensitive equipment like electroencephalogram or electroencephalograph (EEG). Beta waves emanates from brains responsible for problem solving or decision making. Some equipment like neurosky biosensor intercepts these brain waves. In this study, neurosky biosensor is used in measuring the meditation level of students in the physics course. Developed program process the data of neurosky biosensor sent and make decision about meditation level of student in the course. Program says that “your meditation level is low to pass another subject or solve the exam”.